Dinosaur trouble - King-Smith, Dick (Melbourne: Vision Australia Student Support, 2007)
All pterodactyls know that flying dinosaurs are superior, and all apatosauruses know that any dinosaur with only two legs is surely second-class. Nosy, a pterodactyl, and Banty, an apatosaurus, become great friends even though their parents have forbidden them to play together. With Nosy's fast flying and Banty's smarts, the two take on the biggest predator on the Great Plain, and conquer their parents' prejudices in one great adventure